A Cross-sectional study on prevalence and effects of pituitary siderosis on the endocrine status in pediatric patients with transfusion-dependent beta thalassemia - Soheeb, Khadeja Mohamed; Darwish, Ahmad; AL-Rahman, Ashraf Mohamed Abd; Zedan, Magdy Mohamed; Elsharkawy, Ashraf Abd Elmoneim (International Journal of Innovative Research and Scientific Studies, 2025)
Transfusion-dependent β-thalassemia (TDT) is commonly associated with iron overload and multiple endocrine complications. The aim of the work was to investigate the prevalence and the relationship between pituitary siderosis assessed by magnetic resonance imaging (MRI T2*) and endocrinopathy in pediatric patients with TDT. Forty-two TDT patients, ages 10 to 18, were joined in this cross-sectional study from Mansoura University Children's Hospital in Egypt. Anthropometric evaluation, Tanner staging, laboratory tests and MRI T2* for iron overload assessment were performed. The mean age was 13.7 years and 54.8% were female. Mean height was 148.6 cm: 16.7%. Mean weight was 41.3 kg; Mean BMI was 18.3 kg/m². Hypogonadism (52.4%), short stature (33.3%), and hypothyroidism (26.2%) were the most common endocrine complications. Mean hepcidin/ferritin ratio was 0.13. MRI T2*: Mean was 21.7 ms. The hepcidin/ferritin ratio outperformed ferritin and transferrin saturation in terms of accuracy in distinguishing severity levels. Patients with transfusion-dependent β-thalassemia were more likely to experience hypogonadism, hypothyroidism, and short stature. Hepcidin/Ferritin ratio was highly correlated with MRI T2* severity. The Hepcidin/Ferritin ratio emerged as the most accurate non-invasive marker for assessing disease severity and short stature risk.